Computer organization and design : the hardware/software interface - Patterson, David A. (Morgan Kaufmann Series in Computer Architecture and Design., 2009)
The classic textbook for computer systems analysis and design, 'Computer Organization and Design', has been thoroughly updated to provide a new focus on the revolutionary change taking place in industry today: the switch from uniprocessor to multicore microprocessors.